Improved Resource Utilization at a Kraft Pulp Mill - A case study of Södra Cell Värö - Hedlund, Joel; Ullgren, William (My University, 2015)
The Södra Cell Värö kraft pulp mill will during 2015 and 2016 be expanded to increase the pulp production capacity. The increased pulp production will generate an even larger amount of by-products and excess heat from the process, thus likely to increase the amount of unused resources compared with the current situation. This master thesis work is an investigation of different alternative solutions to increase the resource utilization at Värö, and by that increase the mill’s economic profitability and environmental performance. A base case of the expanded pulp mill’s energy system was modelled and used as a reference case for the alternative solutions. The following alternatives for increased resource utilization were examined: bark burning, lignin extraction, increased district heating deliveries to Varberg and Kungsbacka, and increased bark drying to use as fuel in the lime kiln. The evaluation was done with respect to energy and mass balances and by using three key performance indicators; resource efficiency, economic performance and CO2 emissions. Furthermore, a description of other possible solutions, which for different reasons were discarded earlier in the work, was made. Several of these solutions showed great potential for further studies. With respect to the economic performance all the alternatives, except increased bark drying, which was not included in the economic analysis; and bark burning, showed better results than the base case. With respect to resource efficiency lignin extraction generally showed the best results. The CO2 emission balances differed a lot for the different alternatives depending on assumptions regarding the surrounding energy system. The investigation showed that all alternatives, except for bark burning, overall gave better results than the base case and implementing anyone of these alternatives would result in increased resource utilization at the Södra Cell Värö pulp mill.
Keywords: Energi; Hållbar utveckling; Annan kemiteknik; Energy; Sustainable Development; Other Chemical Engineering